Kontroversi Hukum Rokok dalam Kitab Irsyād Al-Ikhwān Karya Syekh Ihsan Muhammad Dahlan - R. Aris Hidayat (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2015)
Fatwa MUI on illicit nature of cigarettes, sparking a debate in the public. Polemics involving the government, tobacco companies, tobacco farmers, cigarette consumers, clergy, health organizations and other community elements. Polemic about the law of cigarettes, according to the search on the manuscript, actually has been going on long before the fatwa MUI. It can be seen on a manuscript entitled Irsyad Al-Ikhwan, work of Sheikh Ihsan Muhammad Dahlan of Boarding Schools (Pondok Pesantren) Jampes Kediri East Java. According to Sheikh Ihsan, the legal position of smoking is found only opinions / ijtihad of the scholars alone, that would be deviation (there is a difference of opinion). Smoking is not a single legal position, some have argued haram, halal, permissible, and even beneficial makruh. It happens because there is a precondition in the case of smoking.—Fatwa MUI tentang sifat bahaya rokok, memicu perdebatan di masyarakat, yaitu polemik yang melibatkan pemerintah, perusahaan tembakau, petani tembakau, konsumen rokok, kyai atau tokoh agama, organisasi kesehatan dan elemen masyarakat lainnya. Polemik tentang hukum rokok, menurut hasil pencarian naskahnya, sebenarnya sudah terjadi jauh sebelum fatwa MUI dikeluarkan. Hal itu bisa dilihat pada manuskrip yang berjudul Irsyad Al-Ikhwan, karya Sheikh Ihsan Muhammad Dahlan dari Pondok Pesantren Jampes Kediri Jawa Timur. Menurut Sheikh Ihsan, posisi hukum merokok hanya merupakan opini / ijtihad para ulama saja, sehingga menimbulkan perbedaan pendapat. Posisi hukum merokok tidaklah tunggal, ada yang berpendapat haram, halal, diperbolehkan, dan bahkan makruh. Itu terjadi karena ada prasyarat dalam kasus merokok.